2016
DOI: 10.1039/c5cp05959c
|View full text |Cite
|
Sign up to set email alerts
|

Role of electrostatic interactions in the adsorption kinetics of nanoparticles at fluid–fluid interfaces

Abstract: The adsorption of particles to the fluid-fluid interface is a key factor for the stabilization of fluid-fluid interfaces such as those found in emulsions, foams and bijels. However, for the formation of stable particle-laden interfaces, the particles must migrate to the interface from the bulk. Recent studies show that the adsorption of particles to the interface formed during emulsification is influenced by the surface charge of the particles. To further investigate this phenomenon, we study the effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 46 publications
0
84
0
Order By: Relevance
“…These adsorption kinetics are in good agreement with previous ndings on CNC adsorption at the A/W interface. 12 Nanoparticle adsorption comprises two underlying subprocesses: 19,20 (i) diffusion limited transport to the interface and (ii) kinetically limited particle adsorption. In the case of charged nanoparticles, the kinetic adsorption barrier may be decreased by salt-induced charge screening, as demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These adsorption kinetics are in good agreement with previous ndings on CNC adsorption at the A/W interface. 12 Nanoparticle adsorption comprises two underlying subprocesses: 19,20 (i) diffusion limited transport to the interface and (ii) kinetically limited particle adsorption. In the case of charged nanoparticles, the kinetic adsorption barrier may be decreased by salt-induced charge screening, as demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In adsorption experiments, the colloidal interactions between the interface (which may carry electrostatic charges) and the charges on the particle may also influence the efficiency of the adsorption 22 , and this was not considered here. In the present work we only consider dynamics once the particle breaches the interface, when capillary energy is expected to be- It can be hypothesised that the origin of the contact line pinning lies in small surface heterogeneities.…”
Section: Cryosem Measurementsmentioning
confidence: 99%
“…For spherical particles, the adsorption energies and kinetics have been inferred from measurements of the interfacial tension using a pendant drop apparatus. Effects of particle size 21 and surface charge 22 on the global adsorption kinetics have been investigated. Using holographic microscopy Kaz et al monitored the adsorption of single particles and observed that the fast initial adsorption was followed by an intriguing and unexpectedly slow relaxation 23 , which was been attributed to surface defects and contact line pinning 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency parameter a is included to represent an energetic barrier to platelet adsorption. 24,25,52 In practice, when fitting the model to experimental data, it appeared that a and k detach were correlated adjustable parameters. In what follows, a was set at 0.5 and the detachment rate constant used as an adjustable parameter.…”
Section: Kinetics Of Emulsificationmentioning
confidence: 99%
“…In the present system and those discussed above this is not found to be the case, therefore there may be some as yet unconsidered factor preventing full surface coverage. Previously reported factors that may affect particle adsorption at the interface include electrostatic barriers, 24,25 mass transport of particles 6,26 and particle aggregation. 14,22 Upon consideration of experimental findings and the energies involved (see ESI, † for calculations) we find that in conditions pertaining to our experiments it is likely that particles may be forced both onto and off the interface during high shear mixing, despite desorption not occurring under quiescent conditions.…”
Section: Introductionmentioning
confidence: 99%